Efficacy and safety of intranasal insulin on postoperative cognitive dysfunction in elderly patients after laparoscopic radical resection of colorectal cancer: a double-blind pilot study - Zhang, Hailong; Zhao, Liqin; Li, Min; Li, Xu; Li, Ruofan; Wu, Di (Frontiers in Aging Neuroscience, 2024)
Objective To evaluate the efficacy and safety of intranasal insulin on postoperative cognitive dysfunction (POCD) in elderly patients after laparoscopic radical resection of colorectal cancer. Methods Older patients scheduled for laparoscopic radical resection of colorectal cancer at Beijing Luhe Hospital, Capital Medical University, between August 2023 and November 2023, were enrolled in this double-blind pilot study. Patients were randomized to the control and insulin groups at a 1:1 ratio. The primary outcome was the rate of POCD at postoperative 7 days. Results A total of 61 patients (30 in the insulin group) were analyzed. The insulin group had a significantly lower POCD rate compared with the control group at postoperative day 7 [4(13.3%) vs. 12 (38.7%), p = 0.024]. The serum levels of IL-6, TNF-α and S100β at T2-5 in the insulin group were significantly lower than those of the control group (IL-6: mean difference at T2, −4.14, p = 0.036; T3, −3.84, p = 0.039; T4, −3.37, p = 0.013; T5, −2.57, p = 0.042; TNF-α: mean difference at T2, −3.19, p = 0.002; T3, −2.35, p = 0.028; T4, −2.30, p = 0.019; T5, −1.96, p = 0.0181; S100β: mean difference at T2, −8.30, p = 0.019; T3, −23.95, p = 0.020; T4, −20.01, p = 0.023; T5, −17.67, p = 0.010). No insulin allergic reactions, nasal irritation, or hypoglycemic reactions were observed in either of the groups. Conclusion Intranasal insulin may decrease the risk of POCD and inhibit the elevated serum IL-6, TNF-α, and S100β levels in elderly patients after laparoscopic radical resection of colorectal cancer, which proves that intranasal insulin may be a promising therapeutic option for POCD. Clinical trial registration Identifier, ChiCTR2300074423.